Analysis Of The Moral Message In The Film Srimulat: Hil Yang Mustahal - Lesmana, Sandi Putra; Hariyanto, Didik (Procedia of Social Sciences and Humanities, 2024)
The primary objective of this research is to investigate the implicit moral messages conveyed in the film "Srimulat: The Impossible Dream" through the application of a descriptive qualitative methodology employing Roland Barthes' semiotic approach. The film is viewed not only as a form of entertainment but also as a communication medium utilized to impart moral, motivational, and inspirational messages to its audience. "Srimulat: The Impossible Dream" depicts the journey of the comedy group Srimulat, based in Surakarta, as they begin their performances at the Sriwedari Theater. Data collection techniques include direct observation of the film and documentation from various sources. Through the analysis of visual signs and texts in several scenes, this research reveals how moral messages are presented within the narrative context of the film. The findings show how the characters in the film experience growth and learn from the conflicts they face. The analysis results show that this film conveys four moral messages in line with Barthes' theory: humility, introspection, self-confidence, and honesty and responsibility. These messages are seen through denotative and connotative signs. For example, an artist must be humble and introspective, believe in his own abilities, and maintain honesty and responsibility. Barthes' semiotic analysis shows that these moral messages are conveyed strongly and effectively, making the film not only entertaining but also providing an in-depth view of moral values in everyday life